Kewenangan Kepala Daerah dalam Perspektif Asas Legalitas dan Checks and Balances dalam Sistem Pemerintahan Daerah di Indonesia - Putriana Paulina Dheri; Wiwik Harjanti (Lembaga Teewan Journal Solutions, 2026)
This study aims to analyze the authority of regional heads from the perspective of the principle of legality and evaluate the effectiveness of the checks and balances mechanism in the regional government system in Indonesia. The study uses normative legal methods with statutory, conceptual, and case-based approaches, through an analysis of the 1945 Constitution of the Republic of Indonesia, Law Number 23 of 2014 concerning Regional Government, Law Number 30 of 2014 concerning Government Administration, as well as related regulations and court decisions. The results show that, normatively, the authority of regional heads has been limited through the principle of attribution, the division of government affairs, and the prohibition of abuse of authority, as a manifestation of the principle of legality in a state governed by law. However, the effectiveness of controlling this authority still faces challenges in implementation, particularly in optimizing the oversight function of the Regional People's Representative Council (DPRD), vertical oversight of the central government, and judicial control. Therefore, strengthening institutional integrity, more measurable limitations on discretion, and consistent law enforcement are essential prerequisites for realizing a democratic and accountable balance of power in regional government.